Mitochondrial markers reveal deep population subdivision in the European protected spider Macrothele calpeiana (Walckenaer, 1805) (Araneae, Hexathelidae) - Arnedo, Miquel A.; Ferrandez, Miguel-Angel (CONSERVATION GENETICS, 2007)
The funnel-web spider genus Macrothele is the only representative of the mygalomorph family Hexathelidae not found in Australia or New Zealand. Its 26 species occur in Central Africa and the Oriental region. Two Macrothele species are found in Europe: M. cretica Kulczynski, 1903 from Crete, and M. calpeiana (Walckenaer, 1805) type species of the genus and the largest European spider, whose distribution extends across the south-eastern Iberian Peninsula, and in two localities of North Africa. Macrothele calpeiana is the only spider protected under European legislation. The fragmentation and destruction of the cork oak forest, with which M. calpeiana was thought to be closely associated, prompted the inclusion of this species in the Bern Convention. Some authors, however, have challenged this view and consider M. calpeiana to be neither a cork oak forest bioindicator nor an endangered species. By contrast, other observations suggest that the distribution of the species is extremely fragmented and that most local populations should be considered as threatened. In this paper, we examine aspects of the conservation status of M. calpeiana in the light of molecular phylogenetic analyses based on mitochondrial markers of sample specimens from major populations. Our data confirm the fragmented distribution of M. calpeiana and reveal high levels of genetic differentiation across its populations. Local population growth cannot be ruled out, though the lineage as a whole has apparently not undergone population growth. Lineage age estimates suggest that M. calpeiana colonized the Iberian Peninsula during the Messinian salinity crisis and that the current population fragmentation originates from the Pliocene and Pleistocene. We argue that the fragmentation and deep genetic divergence across populations, along with evolutionary singularity and endemicity in one of Europe's main biodiversity hotspots, support the preservation of its legally protected status.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Betic-Rifean region; iberian peninsula; mitochondrial genetic variation; population fragmentation; spider conservation